Medial branch nerve block and ablation as a novel approach to pain related to vertebral compression fracture. Issue 5 (October 2016) - Solberg, Joseph; Copenhaver, David; Fishman, Scott M.
Abstract : Purpose of review: This review offers a critical examination of the biomechanical model that posits the posterior elements as a substantial contributor to pain in vertebral fracture. Further, the review assesses the treatment of posterior-element-associated pain in the setting of vertebral compression fracture in relation to vertebral augmentation. Recent findings: In 2015, the only prospective randomized trial comparing percutaneous vertebroplasty with facet blockade was published in which authors found that percutaneous vertebroplasty produced better pain relief and function based on Oswestry Disability Index, Roland Morris Disability Questionnaire, and visual analog scale in the short term (⩽1 week). However, differences in pain relief at 1 month and 12 months were not statistically significant. Summary: The posterior elements may play a significant role in the pain generated after vertebral compression fractures. Treatment of the posterior element pain through medial branch radiofrequency ablation or facet injections may be another tool in providing analgesia in those with pain after vertebral compression fractures.